(untitled) (Journal of the Sylhet Agricultural University, 2025)
The use of antibiotics in the broiler production has elevated concerns due to their potential negative impact on the health of human. Initial studies suggest that medicinal plants may offer a safer alternative, though limited research has been conducted in Bangladesh. The aims of the present experiment were to compare the impacts of licorice powder, antibiotics and probiotics on the growth, vital organs, and blood profiles of broiler. About 180-day-old Lohman Meat chicks were obtained from the Quality Hatchery Limited and equally divided into four groups with three replicates per group, and each replicate consisting fifteen chicks) using a rearing floor litter system. A basal diet was supplied during experiment; T0, control group- no feed additive supply, and treatment group; T1, - 1gm Licorice Powder (LP)/1L of drinking water (DW); T2- 1 gm of antibiotics/1L of DW and T3- 1gm of probiotics/1L of DW. Body weight of each individual birds was recorded weekly, FCR, organ weights, and carcass yields were calculated at the end of the experiment. Blood sample collected from birds on day 35 were analyzed for blood profiles. Data were analyzed using single-factor ANOVA at a 5% significance level. Body weight significantly varied by groups within each of defined days 14, 21, 28, and 35 (p<0.05), with the highest body weight gain in the T1 (licorice powder) group (p>0.05). The FCR was significantly lower in the T1 treated group and T3 treated group (p<0.05). There was no variation found in the change of various organ weight among treated and untreated group of broiler chicken. The hematological parameters were significantly greater in the treated group T3, followed by T1 and lower in the T2 groups compared to the control group T0 (P>0.05). The mean value of ALT was significantly lower in T3 (7. 16 u/l), followed by T2 (7.88 u/l) and T1 (7.94 u/l) than T0; ALP was lower in T1, T2, T3 respectively, total protein, cholesterol. The mean value of HDL was significant higher in T3 (68.35mg/dl) followed by T2 (60.31mg/dl) and T1(46.79mg/dl) than the T0 group (p> 0.01). The administration of licorice powder (T1) and probiotics (T3) resulted in positive impacts on body weight, organs weight and blood profiles of broiler chicks compared to antibiotics (T2). Licorice powder may be suggested as a suitable substitute to antibiotics in poultry production. J. Sylhet Agril. Univ. 11(2): 29-34, 2024